Peran Alumni Al-Azhar Dalam Menyebarkan Islam Moderat Di Indonesia (Prof. Quraish Shihab Dan Ust. Abdul Somad) - Alfarisi, Aldy (Riviera Publishing, 2025)
This article examines the role of Al-Azhar alumni, especially the two figures, namely Quraish Shihab and Abdul Somad Batubara in their da'wah to spread Islam that is rahmatan lil alamin in Bumi Nusantra. Both were born from the same womb that formed the basis of his da'wah thinking and method, namely the Al-Azhar campus. With a diversity of customs and pluralistic cultures, religious moderation here is understood as a religious attitude and view that prioritizes balance, justice, tolerance, and rejects all forms of extremism, both those that lead to radicalism and liberalism. This study uses a qualitative descriptive research approach with literature research. In the data collection technique, the author examined books related to moderation or wasathiyah which consisted of primary data, namely the works of al-Qardhawi, Quraish Shihab, Abdul Somad which were related to manhaj al-wasa?iy. Meanwhile, secondary data are books, articles, and social media videos that are spread about moderation in religion which are the result of the interpretation of others related to the object of this study. This research is expected to provide insight into the role of Al-Azhar alumni in shaping the face of moderate Islam in Indonesia and contribute to socio-religious studies related to the diversity of da'wah approaches in Islamic organizations.